Associations of Blood Urate Level with Glycemic Status and Other Cardiometabolic Risk Factors in Middle-Aged Women - Ichiro Wakabayashi; Takashi Daimon (Mary Ann Liebert, 2021)
Background: Hyperuricemia is a risk factor of cardiovascular disease. It remains to be elucidated how blood urate level is associated with hyperglycemia in women. Methods: The participants were 4612 middle-aged Japanese female workers. They were divided into four quartile groups by serum urate level, and cardiovascular risk factors were compared in the quartile groups. Results: With an increase of the quartile for urate, the means of waist-to-height ratio, systolic and diastolic blood pressure, log-transformed triglycerides, low-density lipoprotein (LDL) cholesterol, and cardiometabolic index (CMI) tended to be higher and high-density lipoprotein (HDL) cholesterol tended to be lower. Hemoglobin A1c was significantly higher in the 4th quartile for urate than in the 1st quartile, but this difference was not found when body mass index (BMI) was adjusted. The odds ratios versus the 1st quartile for high waist-to-height ratio, hypertension, hypertriglyceridemia, hypo-HDL cholesterolemia, hyper-LDL cholesterolemia, high CMI, and diabetes tended to be higher with an increase of the quartile. The odds ratios of the 4th versus 1st quartiles for these abnormalities except for high waist-to-height ratio and diabetes were significantly higher than the reference level even with adjustment for BMI. Hemoglobin A1c showed a weak but significant positive correlation with urate in analysis with adjustment for BMI. Conclusion: Blood urate was positively associated with adiposity, blood pressure, triglycerides, LDL cholesterol, and glycemic status and was inversely associated with HDL cholesterol in middle-aged women. The associations of urate with blood pressure, blood lipids, and glycemic status remained independent of adiposity, although being confounded by adiposity.